2013
DOI: 10.1055/s-0033-1350516
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI: T2-Mapping Versus T2-Weighted Dark-Blood TSE Imaging for Myocardial Edema Visualization in Acute Myocardial Infarction

Abstract: Purpose: To assess the diagnostic accuracy of T2 mapping for the detection of myocardial edema in acute myocardial infarction (AMI), and to compare this diagnostic accuracy with that of the current standard for myocardial edema imaging, which is T2w dark-blood TSE imaging. Materials and Methods: 29 patients with AMI were examined at 1.5?T. For the visualization of myocardial edema, T2 maps, calculated from three T2w SSFP images, and T2w dark-blood TSE images were acquired in standard short- and long-axis view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Moreover, while correct interpretation of standard qualitative T2-w images is challenging in global edema due to the lack of healthy reference tissue, we demonstrated that diffuse myocardial edema as seen in patient #2 can be detected more easily with myocardial T2 mapping compared to qualitative T2-w imaging. Although some clinical studies already investigated the diagnostic value of myocardial T2 mapping in acute myocardial injury [ 11 , 25 , 28 ] more studies with well-defined study populations will be necessary to evaluate the clinic impact of myocardial T2 mapping [ 26 ]. Especially studies, with well-defined cohorts that use a longitudinal design will be necessary to investigate the benefits for monitoring therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while correct interpretation of standard qualitative T2-w images is challenging in global edema due to the lack of healthy reference tissue, we demonstrated that diffuse myocardial edema as seen in patient #2 can be detected more easily with myocardial T2 mapping compared to qualitative T2-w imaging. Although some clinical studies already investigated the diagnostic value of myocardial T2 mapping in acute myocardial injury [ 11 , 25 , 28 ] more studies with well-defined study populations will be necessary to evaluate the clinic impact of myocardial T2 mapping [ 26 ]. Especially studies, with well-defined cohorts that use a longitudinal design will be necessary to investigate the benefits for monitoring therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Mild and limited cutaneous SSc might present with less pathologic CMR findings per individual. No T 2 imaging was performed, but non-quantitative T 2 imaging cannot reliably depict diffuse edema [ 35 , 36 ] and edema has not been found in previous reports [ 10 ]. Neither T 1 nor T 2 - mapping were available at the time patients were examined.…”
Section: Discussionmentioning
confidence: 99%
“…values instead of differences in relative signal intensities (161). In fact T1 mapping may have superior performance to T2 mapping for the detection of acute myocardial oedema (162).…”
Section: Cmr Detection Of Oedemamentioning
confidence: 99%